Conflict-Induced Displacement and Food Insecurity: The Case Of Burkina Faso As Sahel’s Growing Epicenter of Conflict - Putu Prisca Lusiani; Yodana Nisadina (Journal of Islamic World and Politics, 2024)
This article discusses how the military conflict in Burkina Faso affects food insecurity and the welfare of its people. This issue poses a threat to its citizens' ability to achieve human security, which focuses on welfare and basic human rights, including the availability and access to adequate food. This article is qualitative research, and the analysis of this phenomenon comes from reference articles, books, news, reports, and official documents. The theoretical approach used is related to Conflict-Induced Displacement, Human Security, and the four main dimensions of Food Security, namely food availability, access, utilization, stability, and displacement of communities due to conflict. The results of the analysis show that the geographic location of the country of Burkina Faso, which is confined between the West African mainland, makes it vulnerable to military conflict affiliated with Jamaat Nusrat al-Islam wal-Muslimin (JNIM) and is now the center of conflict in the Sahel region. The author also found out that the main reason for ongoing hunger and malnutrition in Burkina Faso is because its people were forced to be displaced due to armed conflict in the region.